Representasi Ageing dalam Film "Hello, My Name is Doris" - Fat’Hiyyah Asya Fakhriyah (Jurnal Ilmu Komunikasi, 2021)
Aging at this time is still something that is avoided by many people, even though aging will certainly happen to all humans. Aging is often considered a period of decline because many things change, from physical to mental conditions. This also happens in the realm of Hollywood. Actresses over the age of 60 are considered difficult to get interesting roles. The role that can be obtained is only the role of a companion as a wife, mother or grandmother. One of the movies that still uses elderly actresses as the main character is Hello, My Name is Doris, which was released in 2015. This research is a qualitative research using a literature study method. To find out the representation of aging in the film Hello, My Name is Doris, Roland Barthes' semiotic theory is used. The results of this study indicate that aging is not only represented negatively but also positively in the Hello, My Name is Doris.